Management of complications after total shoulder arthroplasty - Eichinger, Josef K. (Curr Rev Musculoskelet Med, 2015)
The outcomes of total shoulder arthroplasty (TSA) for painful arthritis of the glenohumeral joint are excellent with significant improvement in pain and function. Increased use of total shoulder arthroplasty over the past decade has led to identification of common complications. Although the complication rate is low, accurate and timely diagnosis, appropriate management, and implementation of methods for prevention are critical to a successful long-term outcome. The most common complications include infection, glenoid and humeral component loosening, rotator cuff tear, periprosthetic fracture, and neurologic injury. The purpose of this review is to outline the best practices for diagnosing, managing, and preventing these complications.